Benign papillary cystadenofibroma of fallopian tube presenting as posterior fornix cyst: case report - Narayanrao, Gude Prajakta; Srinivasan, P. V.; Kala, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Benign papillary cystadenofibroma of fallopian tube is very rare tumor of female genital tract. Usually asymptomatic and incidental finding. Worldwide literature only 18 cases were found. On account of its rarity and best of our knowledge, is the first case of benign papillary cystadenofiboma presented as posterior fornix cyst, so we are presenting this case. We report a rare case of benign papillary cystadenofibroma of fallopian tube in a 30-years old female P3L3 presenting with abdominal pain. On examination abdomen was soft, per vaginally mobile non-tender cystic mass of 5×4 cm was noted. Laparotomy was planned. Intraoperatively 5x4 cm cyst arising from serosal surface of left fallopian tube near fimbrial end noted with bilateral ovaries normal. Left fimbrial cystectomy with salpingectomy was done with sparing both ovaries. Histopathology suggestive of benign papillary cystadenofibroma of fallopian tube. Patient had uneventful recovery in follow up period. Benign papillary cystadenofibroma of fallopian tube is rare tumor found incidentally. Tumor seems to have benign course only cystectomy is required for treatment.